PREPARATION OF CESIUM LEAD HALIDE PEROVSKITE NANOCRYSTALS AND THE STUDY OF THEIR SURFACE STATES AND OPTICAL CHARACTERISTICS INFLUENCED BY SURFACE LIGAND - Asharuddin, Muhammad
All-inorganic cesium lead halide (CsPbX3, where X= Cl, Br, or I) perovskites have recently garnered significant interest owing to their unique optical properties with strong photoluminescence (PL), making them promising candidates for optoelectronic applications. Various synthesis methods used for preparing halide perovskites in the form of quantum dots (QDs) and nanocrystals (NCs) have been reported, such as ligand-assisted reprecipitation (LARP) and ultrasonic-assisted (URSOA) methods. In this thesis, we report the preparation of NCs of CsPbBr3 perovskites, which were prepared by the LARP and URSOA methods, and the investigation of the ligand effects on their crystal structure, surface chemical states and optical properties. For the CsPbBr3NCs prepared using LARP method, X-ray diffraction (XRD) showed the bulk crystal structures did not change after the removal of ligands from the NC surface by purification. According to X-ray photoelectron spectroscopy (XPS), it was found that the chemical state of NC surface became less uniform, with unbonded Pb atoms and Cs atom accumulations were formed after purification. Thus, the NCs with the purification showed weaker PL intensity than the NCs without the purification. Similar results were also observed for NCs prepared using the URSOA method, wherein the NCs with and without ligands have the same bulk crystal structures, but the NCs without ligands exhibit weaker PL intensity than the NCs with ligands. The present results highlight the crucial role of ligands and surface chemical states on the PL characteristics of these perovskite NCs, which will be critical in determining their applications in optoelectronic devices.